Large Differences in Bacterial Community Composition among Three Nearby Extreme Waterbodies of the High Andean Plateau - Aguilar, Pablo; Acosta, Eduardo; Dorador, Cristina; Sommaruga, Ruben (Frontiers in Microbiology, 2016)
The high Andean plateau or Altiplano contains different waterbodies that are subjected to extreme fluctuations in abiotic conditions on a daily and annual scale. The bacterial diversity and community composition of those shallow waterbodies is largely unexplored, particularly, of the ponds embedded within the peatland landscape (i.e., Bofedales). Here we compare the small scale spatial variability (<1 m) in bacterial diversity and community composition between two of those ponds with contrasting apparent color, using 454 pyrosequencing of the 16S rRNA gene. Further, we compared the results with the nearest (80 m) main lagoon in the system to elucidate the importance of different environmental factors such as salinity and the importance of these ponds as a source of shared diversity. Bacterial diversity was higher in both ponds than in the lagoon and community composition was largely different among them and characterized by very low OTU sharing. Whereas the “green” pond with relatively low DOC concentration (33.5 mg L-1) was dominated by Proteobacteria and Bacteroidetes, the one with extreme DOC concentration (424.1 mg L-1) and red hue was dominated by Cyanobacteria. By contrast, the lagoon was largely dominated by Proteobacteria, particularly by Gammaproteobacteria. A large percentage (47%) of all reads was unclassified suggesting the existence of large undiscovered bacterial diversity. Our results suggest that even at the very small scale spatial range considered, local environmental factors are important in explaining differences in bacterial community composition in those systems. Further, our study highlight that Altiplano peatland ponds represent a hitherto unknown source of microbial diversity.